5а - 3с ах 5а - 3с ах
------------ = ---------- ⇒ ------------------------ = -----------------
25а²-9с² 10а+6с (5а - 3с )(5а + 3с ) 2(5а+3с)
1 ах
------------- = -------------- ⇒ 1*2(5а+3с) =ах*(5а+3с) сократим обе части
(5а + 3с ) 2(5а+3с)
2=ах ⇒ х=2/а
------------------------------------------------------------------------------------------------------
2а-3b x*(3b-2a)
--------- = --------------- ⇒ (2a-3b)*ab² = -x*(2a-3b)*a²b сократим обе части
a²b ab²
на (2a-3b)*ab , получим b= -x*a x=-b/a
---------------------------------------------------------------------------------------------------
a⁴-a a²+a+1 а (а³-1) а²+а+1
------------ = ------------ ⇒ -------------- = ----------- ⇒
2a²-2a x 2а*(a- 1) х
а (а -1)*(а²+а+1) а²+а+1 (а²+а+1) а²+а+1
------------------------- = ------------ ⇒ -------------- = ---------------- ⇒
2а*(a- 1) х 2 х
х*(а²+а+1 ) =2*(а²+а+1 ) сократим , х=2